Ab initio study of (Fe, Ni) doped GaAs: Magnetic, electronic properties and Faraday rotation. (June 2017) - Sbai, Y.; Ait Raiss, A.; Bahmad, L.; Benyoussef, A.
Abstract: The interesting diluted magnetic semiconductor (DMS), Gallium Arsenide (GaAs), was doped with the transition metals magnetic impurities: iron (Fe) and Nickel (Ni), in one hand to study the magnetic and magneto-optical properties of the material Ga(Fe, Ni) As, in the other hand to investigate the effect of the doping on the properties of this material, the calculations were performed within the spin polarized density functional theory (DFT) and generalized gradient approximation (GGA) with AKAI KKR-CPA method, the density of states (DOS) for different doping concentrations were calculated, giving the electronical properties, as well as the magnetic state and magnetic states energy, also the effect of these magnetic impurities on the Faraday rotation as magneto-optical property. Furthermore, we found the stable magnetic state for our doped material GaAs. Highlights: Ab-initio calculations were performed to study our GaAs compound. Density of states (DOS) were calculated and plotted for each doping concentration. Density of states (DOS) were calculated and plotted for each doping concentration. GGA approximation has been performed in the ab initio calculations for better precision.